PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN TEGAL SARI ACCOMMODATIONDI UBUD - Ni Putu Sawitri; Ni Nyoman Kerti Yasa; Abdulah Jawas (Faculty of Economics and Business Udayana University, 2013)
The aim of this research is to know the effect of service quality towards customer satisfaction and loyalty in Tegal Sari Accommodation Ubud. Respondent of this research are foreign customer with at least 17 years oldwho remain to stay at Tegal Sari Accommodation at least twice in the last 5 years. The number of respondents on this research defined 140 respondents by using sampling technique that is purposive sampling. This research used analysis of Structural Equation Modeling (SEM) with the help of AMOS program. The result of this research showed that service quality has significant impact on satisfaction, satisfaction has significant impact on loyalty, service quality has significant impact on loyalty of Tegal Sari Accommodation Ubud.